2017
DOI: 10.1007/s00280-017-3408-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent paclitaxel, capecitabine, mitomycin C and pelvic radiation therapy for patients with squamous cell anal carcinoma

Abstract: Investigated treatment scheme is feasible despite high toxicity profile, and may be beneficial for patients with advanced SCAC. Further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Concurrent chemo and radiation therapies (CRT) is a standard treatment for many solid tumors, especially locally advanced cancers [67]. Many chemotherapeutants, such as cisplatin, docetaxel, and 5-fluorouracil, have been identified as radiosensitizers to improve local control and survival rates, while potentially eradicating distant micrometastatic disease [68][69][70]. However, concurrent chemoradiation causes more serious side effects, compared with therapy alone or sequential RT and chemotherapy [71].…”
Section: Nanomaterials For Combined Chemotherapy and Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent chemo and radiation therapies (CRT) is a standard treatment for many solid tumors, especially locally advanced cancers [67]. Many chemotherapeutants, such as cisplatin, docetaxel, and 5-fluorouracil, have been identified as radiosensitizers to improve local control and survival rates, while potentially eradicating distant micrometastatic disease [68][69][70]. However, concurrent chemoradiation causes more serious side effects, compared with therapy alone or sequential RT and chemotherapy [71].…”
Section: Nanomaterials For Combined Chemotherapy and Rtmentioning
confidence: 99%
“…It has been found that some traditional chemotherapy drugs can serve as radiosensitizers to increase the efficiency of RT through different mechanisms [68][69][70]. For example, paclitaxel (PTX) can arrest cells at the G2/M phase, which is more sensitive to radiation [68].…”
Section: The Clinical Translation Of Nanomaterials As Radiosensitizersmentioning
confidence: 99%
“…Заболевание преимущественно диагностируют в локализованной или местно-распространенной форме, когда имеются возможности эффективного радикального лечения. Корректное построение врачебной тактики может обеспечить 5-летнюю выживаемость у 80-90 % пациентов с сохранением высокого качества жизни и полноценной трудоспособности [7,[9][10][11]. Нарушение плана лечения приводит к высокой частоте инвалидизации, повышению частоты выполнения калечащих операций и более высокой смертности.…”
Section: ' 2020unclassified
“…Some patients will, however, not be eligible for platinum‐based treatment, and alternative regimens are relevant. Paclitaxel‐based chemotherapy has shown activity in both the chemotherapy‐naive and chemo‐refractory setting in SCCA, 9,10 and the combination regimen of Paclitaxel and Capecitabine has been investigated as a nonplatinum‐based option for head and neck cancer with relevant efficacy and moderate toxicity reported 11 . Theoretically, the combination of Taxanes and Capecitabine also offers reasonable predictable efficacy due to the given mechanism of action, and previous studies have found a synergy in vivo, thought to be caused by Taxane up‐regulating dThdPase and thereby enhancing the efficacy of Capecitabine 12,13 …”
Section: Introductionmentioning
confidence: 99%